The potential of fosfomycin for multi‐drug resistant sepsis: an analysis ofin vitroactivity against invasive paediatric Gram‐negative bacteria. Issue 5 (May 2019) - Williams, Phoebe C. M.; Waichungo, Joseph; Gordon, Claire N.; Sharland, Mike; Murunga, Sheila; Kamau, Alice; Berkley, James A.
Abstract : N/A: P urpose . Antimicrobial resistance (AMR) is of increasing global concern, threatening to undermine recent progress in reducing child and neonatal mortality. Repurposing older antimicrobials is a prominent strategy to combat multidrug‐resistant sepsis. A potential agent is fosfomycin, however, there is scarce data regarding its in vitro activity and pharmacokinetics in the paediatric population. M ethodology . We analysed a contemporary, systematically collected archive of community‐acquired (CA) and hospital‐acquired (HA) paediatric Gram‐negative bacteraemia isolates for their susceptibility to fosfomcyin. MICs were determined using agar serial dilution methods and validated by disk diffusion testing where breakpoints are available. Disk diffusion antimicrobial susceptibility testing was also conducted for current empirical therapies (ampicillin, gentamicin, ceftriaxone) and amikacin (proposed in the literature as a new combination empirical therapeutic option). R esults . Fosfomycin was highly active against invasive Gram‐negative isolates, including 90 % (202/224) of Enterobacteriaceae and 96 % (22/23) of Pseudomonas spp. Fosfomycin showed high sensitivity against both CA isolates (94 %, 142/151) and HA isolates (81 %, 78/96; P =0.0015). CA isolates were significantly more likely to be susceptible to fosfomycin than the current first‐line empirical therapy (96 % vs 59 %, P <0.0001). Extended spectrum β ‐lactamases (ESBL) production was detected in 34 % (85/247) of isolates with no significant difference in fosfomycin susceptibility between ESBL‐positive or ‐negative isolates [73/85 (86 %) vs 147/162 (91 %) respectively, P =0.245]. All isolates were susceptible to a fosfomycin‐amikacin combination. C onclusion . Gram‐negative paediatric bacteraemia isolates are highly susceptible to fosfomycin, which could be combined with aminoglycosides as a new, carbapenem‐sparing regimen to achieve excellent coverage to treat antimicrobial‐resistant neonatal and paediatric sepsis.